LANGUAGE VARIETIES AND TRANSLANGUAGING IN COMMUNICATIVE PRACTICE BETWEEN LECTURER AND STUDENTS IN THE SIXTH SEMESTER OF ENGLISH EDUCATION STUDENTS - Sinaga, Tika Yohana; Pasaribu, Yessy Octavianna; Manurung, Lastri Wahyuni (Dharmas Education Journal (DE_Journal), 2022)
Sociolinguistics is the study of the relationship between language and society, examining how social factors influence language use. This qualitative study investigated the use of translanguaging and language varieties within the sociolinguistic context of communicative practices between lecturers and sixth-semester English Education students at HKBP Nommensen University. The research aimed to identify the types of translanguaging and language varieties employed and to explore their benefits in enhancing classroom communication. Findings revealed that lecturers predominantly utilized language style (16 data) as a form of language variation, reflecting their personal communication approaches. In terms of translanguaging, personal translanguaging (20 data) was most prevalent, indicating a natural integration of multiple linguistic resources. The study highlighted that both language variation and translanguaging significantly improved communication, comprehension, and student engagement. Lecturers and students reported that these practices facilitated the expression of complex ideas, boosted confidence, and fostered a more inclusive learning environment. The research suggests that incorporating translanguaging and language variation, including multilingual resources and the integration of students' first languages, is crucial for optimizing educational outcomes in EFL contexts